(untitled) (Medical Forum Monthly, 2023)
Objective: To observe the frequency, clinical presentation and outcome in the patients of mucormycosis during the waves of COVID 19 pandemic. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at the Department of Otorhinolaryngology, Bahawal Victoria Teaching Hospital, Bahawalpur, from November, 2020 to March, 2022. Materials and Methods: Total 38 diabetic patients with Rhinocerebral mucormycosis which were confirmed through endoscopic, radiological and also histopathological findings. All the patients once diagnosed and included in the study were started with intravenous Amphotericin B after dose adjustment according to the body weight and baseline renal profile. Intravenous antifungal treatment was continued for every patient for the period of 6 to 8 weeks. Clinical outcome in terms of improvement/deterioration in symptoms and signs and mortality were recorded. SPSS version 21 was used for data analysis. Results: The mean age was 51.5±10.55 years. Majority 27 patients were males (71.05%) and 11 were females (28.95%). Out of 38 patients only 16 patients were having the previous history of Covid 19 infection. 31 were having orbital involvement and 6 were having intracranial involvement. 18 patients were histopathologically confirmed as of mucormycosis. 26 patients were recovered after treatment, 10 patients could not survive and expired while 2 patients were lost against medical advice. Conclusion: Patients with diabetes mellitus along with Covid 19 infection are more predisposed to have invasive fungal infection like Mucormycosis. Aggressive intravenous anti-fungal therapy and debridement can reduce patient’s mortality.